Growth and yield response of Tanjung II and Unpad CB2 red chili varieties grown in the medium land - Lestari, Rahma Wati; Kusumiyati, Kusumiyati; Mubarok, Syariful; Maulana, Yusuf Eka (Kultivasi, 2024)
Red chili is an important commodity that is daily needed by the community. Non-central chili areas often experience deficits due to the high consumption volume and low productivity of chili peppers. To increase the productivity of chili in non-central areas, expand it in the medium land. This study aims to determine the productivity of two introduced chili varieties in the medium land whose adaptation areas came from lowland and highland areas. This study was analyzed using an independent sample T-test at a significant level of 5%. The results of the data analysis showed that the Tanjung II variety significantly influenced the parameters of stem diameter and weight of the fruit. Meanwhile, the Unpad CB2 variety significantly influences the parameters of plant height, number of leaves, number of flowers, number of fruits, and fruit set. However, both varieties have no noticeable effect on the weight parameters of the cropping fruit and potential yield in hectares. The Tanjung II variety experienced a decrease in yield by 54.58%, while the Unpad CB2 variety was 53.56%.